O Regimento dos Lagares de Azeite de Coimbra do século XVI. Os agentes e mecanismos de controlo, os objetos e as práticas regulamentadas - Coelho, Maria Helena da Cruz (2022)
In late-medieval Coimbra, the olive oil mills were an important source of income, and their activity was object of an exhaustive regulation, composed by the municipal rules, which were gathered and registered in one document entitled as the Regiment of the olive oil mills and olive oil makers of the city of Coimbra (1554). In this article, the regiment will be framed in the historical and urban context of its production and will be characterised according to its structure and contents. After the presentation of the agents of control, of the craftsmen and other workers object of the norms, of the control strategies identified in the document, we intend to analyse the aspects object of regulations and control. For that, we submitted the document to a detailed analysis in order to understand in what extent this regiment regulated activity aspects such as: the admission of the metier; the access and the maintenance of the equipment; the weights and measures control; prices and wages standardization; theft prevention; preservation of environmental and sanitary conditions.